2013
DOI: 10.2147/opth.s38575
|View full text |Cite
|
Sign up to set email alerts
|

Preference for a fixed combination of brinzolamide/timolol versus dorzolamide/ timolol among patients with open-angle glaucoma or ocular hypertension

Abstract: ObjectiveTo assess ocular discomfort upon instillation and patient preference for brinzolamide/timolol relative to dorzolamide/timolol, in patients with open-angle glaucoma or ocular hypertension.MethodsThis was a multicenter, prospective, patient-masked, randomized, crossover study. On day 0, patients received one drop of brinzolamide/timolol in one eye and one drop of dorzolamide/timolol in the contralateral eye. On day 1, patients were randomly assigned to receive one drop of either brinzolamide/timolol or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
2
13
1
1
Order By: Relevance
“…BRINZ/TIM-FC therapy was associated with significantly greater reductions in IOP compared with TIM monotherapy at the estimated peak (primary endpoint) and trough (secondary endpoint) time points, and it was well tolerated in this study population. Overall, the efficacy and safety profiles of BRINZ/TIM-FC observed in the present study were consistent with those reported in previous investigations of BRINZ/TIM-FC, BRINZ monotherapy, or concomitant BRINZ and TIM therapy in other patient populations 8,21,23,24,27,34,35. The double-masked, randomized design of this study increases the confidence in the findings presented here.…”
Section: Discussionsupporting
confidence: 92%
“…BRINZ/TIM-FC therapy was associated with significantly greater reductions in IOP compared with TIM monotherapy at the estimated peak (primary endpoint) and trough (secondary endpoint) time points, and it was well tolerated in this study population. Overall, the efficacy and safety profiles of BRINZ/TIM-FC observed in the present study were consistent with those reported in previous investigations of BRINZ/TIM-FC, BRINZ monotherapy, or concomitant BRINZ and TIM therapy in other patient populations 8,21,23,24,27,34,35. The double-masked, randomized design of this study increases the confidence in the findings presented here.…”
Section: Discussionsupporting
confidence: 92%
“…The safety and efficacy of BRINZ/TIM-FC and BRINZ + TIM in this study were consistent with those reported in previous studies of these agents as combination therapy and monotherapy in other patient populations 10,11,18,19,21,22,30,31. Similar to the current study, which demonstrated comparable efficacy of BRINZ/TIM-FC and unfixed concomitant BRINZ + TIM, other clinical assessments of fixed-combination therapies have demonstrated that fixed-combination pharmacotherapies containing TIM and dorzolamide, a carbonic anhydrase inhibitor, or latanoprost, a prostaglandin analog, have efficacy similar to that of concomitant treatment with their active components 3235.…”
Section: Discussionsupporting
confidence: 91%
“…However, in a previous multinational noninferiority study conducted in Europe, BRINZ/TIM-FC produced IOP reductions similar to those achieved with fixed-combination dorzolamide 2%/TIM 20. Further, studies conducted in the US and South America indicate that among patients with a treatment preference, BRINZ/TIM-FC was favored by patients over fixed-combination dorzolamide 2%/TIM 21,31. This result may be attributable to the increased severity and duration of ocular discomfort with dorzolamide 2%/TIM compared with BRINZ/TIM-FC 18,21,31,36.…”
Section: Discussionmentioning
confidence: 87%
“…Several previous reports have compared the efficiency and safety of fixed combination therapy, including dorzolamide 2%/timolol 0.5% and brinzolamide 1%/timolol 0.5%, 10 – 17 with many authors reporting similar intraocular pressure (IOP)-lowering efficacy for these treatments. 11 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Regarding patient preferences, some reports have shown that patients prefer brinzolamide 1%/timolol 0.5% when asked an alternative question. 10 , 13 , 16 , 17 However, in clinical practice, we often hesitate over which eye drop to choose because some patients cannot tolerate brinzolamide 1%/timolol 0.5% but can tolerate dorzolamide 1%/timolol 0.5%. We suspect that patients’ real preferences cannot be judged by two selections, and in actuality some patients may be tolerant to both.…”
Section: Introductionmentioning
confidence: 99%